SUDIRMAN SHOPPING CENTER WITH THE USE OF PUBLIC SPACE - Heru Wibowo (Sean Institute, 2022)
Shopping centers have the meaning of a place that is innate with one or several large department stores as an attraction for small retails and malls or pedestrians which are the main elements of a shopping mall with a function as circulation and as a communal space for the implementation of interaction between visitors and merchants. Shopping centers in the modern era with antiquity are very different, modern era shopping centers are designed with retail and supporting facilities to provide comfort in buying and selling activities, while in ancient times (the market) was only designed for buying and selling activities without thinking about the comfort of the activity actors in it. The design of this Shopping center object is not only a place for buying and selling and entertainment. However, it has more important values, ranging from function, beauty, and dynamic, buildings with contemporary architecture with contemporary physical forms of materials and Dynamic Showcase can be interpreted as the attraction of shopping centers as supporting facilities / facilities